Bitin na pantawid an investigative study on PNoy's Pantawid Pasada Program, focusing on public utility jeepneys in Metro Manila - Dela Cruz, Kathlyn Kaye L.; Encanto, Georgina R.; Reyes, Maria Fatima (2012)
"This study reveals how the government's Pantawid Pasada Program, a one-time targeted fuel subsidy given to public utility jeepney (PUJ) drivers in the form of cards loaded with P1,050, failed to meet its objective of assisting drivers in alleviating the ill-effects of the oil crisis. Documentary evidence and interviews with pertinent sources such as officials from the programs's implementing agency Department of Energy (DOE) and leaders from major transport groups show how the incompetence and lack of cooperation displayed by both members of transport groups and government agencies involved in the implementation process contributed greatly to the program's failure. Findings show that out of the 160,000 printed fuel cards, only about 90,000 to 100,000 were distributed to the transport sector, which means that only about 56.3% to 62.5& of the targeted beneficiaries were able to receive the fuel cards, not all of which were loaded with the designated amount. The study also explores the specific reasons why transport groups opposed the program and their proposed long-term solutions to the oil crisis."
Vita.
Undergraduate thesis (A.B. Journalism)--University of the Philippines.
Keywords: Pantawid Pasada Program; Jeep automobile -- Fuel consumption -- Subsidies